Spatial variations in a condensed interval between estuarine and open-marine settings: Holocene Hudson River estuary and adjacent continental shelf - McHugh, C. M. G.; Pekar, S. F.; Christie-Blick, N.; Ryan, W. B. F.; Carbotte, S.; Bell, R. (Geology, 2004)
An interval of stratigraphic condensation extending for 300 km from the fluvially dominated Hudson River estuary to the adjacent continental shelf reveals stratal relationships within an unconformity-rellated depositional sequence that are commonly difficult to resolve in seismic reflection profiles and outcrop. High-resolution side-scan sonar and bathymetry, more than 100 sediment cores similar to2 m long, and radioisotope (C-14, Cs-137) age control show that much of the valley was filled by ca. 3 to 1 ka. The present rate of sediment accumulation averages 1 mm/yr, corresponding with a sea-level rise of similar to1.2 mm/yr relative to local bedrock. Condensation is manifested today by sedimentary bypass in most parts of the estuary and by the trapping of available sediment (1.2-5.6 x 10(5) t/yr [metric tons]) along narrow reaches and primarily in the vicinity of the estuarine turbidity maximum, a part of the estuary located upstream of the salinity intrusion similar to25 km from the mouth (3.0 x 10(5) t/yr). Shelf condensation is due to sediment starvation. The condensed interval merges updip with a nascent sequence boundary as the estuary reaches its final filling phase and downdip with the sequence boundary that developed at the Last Glacial Maximum. Delta progradation may take place as available shelf accommodation is filled, but such sediments are expected to be removed once sea level begins to fall. This sedimentation pattern, in which a condensed interval merges with different sequence boundaries, is consistent with the stratigraphic record of the Atlantic margin back to the Paleogene and may be typical of sediment-starved margins.
772lcTimes Cited:10Cited References Count:30